Mucoadhesive polymers in substance-based medical devices: functional ingredients or what else? - Barbara Vigani; Silvia Rossi; Giuseppina Sandri; Maria Cristina Bonferoni; Carla M. Caramella (Frontiers in Drug Safety and Regulation)
The paper is intended to deal with the regulatory status of the family of substance-based medical devices (SB-MD) which contain mucoadhesive polymers. Mucoadhesive formulations are mainly intended for oral/buccal, gastro-esophageal, nasal, or vaginal administration routes. They contain one or more substances/polymers of either natural, synthetic or semi-synthetic origin endowed with mucoadhesive properties. These are complex substances whose chemical-physical properties are in general well characterized. Hydration and water retaining properties, gel formation, lubricating properties are example of functional characteristics that may be involved in mucosal interaction. However, there are still uncertainties as to the underlaying mechanisms. The idea is to provide support, to the understanding of the prevailing mechanisms of action of the family of SB-MD that exploit mucoadhesion phenomenon to exert the intended therapeutic action. A case study on Hyaluronic acid as a typical representative of mucoadhesive polymers, is presented. The correct understanding of the mechanism of action of the substances/polymers involved in SB-MD is pivotal to a smooth and successful submission to the involved regulatory bodies to a positive assessment and to the final approval.